2019
DOI: 10.15420/ecr.2018.29.2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Platelet Function-Guided Strategy with Clopidogrel or Ticagrelor

Abstract: Some patients treated with dual antiplatelet therapy (DAPT) following acute coronary syndrome (ACS) can still exhibit heightened residual platelet reactivity (HRPR), which is potentially linked to adverse vascular outcomes. Better tailored DAPT strategies are needed to address this medical need. Aim: To assess the cost-effectiveness of guided DAPT with clopidogrel or ticagrelor in addition to aspirin when using VerifyNow P2Y12 testing in post-ACS patients. Methods: The costs were calculated per 1,000 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Nevertheless, dual antiplatelet therapy with clopidogrel and aspirin remains the standard of care for preventing recurrent ischemic events in patients undergoing percutaneous coronary intervention 40 . Clopidogrel is also reportedly associated with a lower bleeding risk than the more recently introduced platelet inhibitors and is less expensive 41 . Hence, personalized clopidogrel dosing regimens for PMs are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, dual antiplatelet therapy with clopidogrel and aspirin remains the standard of care for preventing recurrent ischemic events in patients undergoing percutaneous coronary intervention 40 . Clopidogrel is also reportedly associated with a lower bleeding risk than the more recently introduced platelet inhibitors and is less expensive 41 . Hence, personalized clopidogrel dosing regimens for PMs are needed.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Clopidogrel is also reportedly associated with a lower bleeding risk than the more recently introduced platelet inhibitors and is less expensive. 41 Hence, personalized clopidogrel dosing regimens for PMs are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Lomakin et al . [44] compared platelet function-guided drug selection with universal clopidogrel or ticagrelor and found the guided strategy to be of high economic value (ICER for assay-guided prasugrel vs. universal clopidogrel = $14 460; ICER for assay-guided ticagrelor vs. universal clopidogrel = $16 993).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study by Straub et al[43] found that platelet-function-guided P2Y 12 inhibitor selection was more cost-effective, relative to universal clopidogrel, than were universal ticagrelor or universal prasugrel. Most recently, Lomakin et al[44] compared platelet function-guided drug selection with universal clopidogrel or ticagrelor and found the guided strategy to be of high economic value (ICER for assay-guided prasugrel vs. universal clopidogrel = $14 460; ICER for assayguided ticagrelor vs. universal clopidogrel = $16 993). MI.…”
mentioning
confidence: 99%
“…In the current edition of European Cardiology Review, a simulated analysis of DAPT post-ACS driven by testing for platelet reactivity gives some hope that a personalised approach to anti-platelet therapy is still worth exploring. 9 We believe that the randomised trial evidence mentioned above is too convincing to resurrect this approach. p=0.002 for the presence of two LOF alleles).…”
mentioning
confidence: 99%